Hypothyroidism in Vitiligo Patient: A Case Report - Bhandari, Anjali; Joshi, Rajesh Dhoj; Dahal, Abhinav; Palikhe, Muna; Shrestha, Suman; Shah, Shyam Sundar; Onta, Astha; Aryal, Aisa (Annapurna Journal of Health Sciences, 2025)
Hypothyroidism is a disease condition in which thyroid hormones in the body are low. Vitiligo is the condition in which there is autoimmune loss of melanocytes resulting in depigmented lesions. Different genetic factors and certain environmental factors triggers have been found to initiate the disease process. The prevalence of hypothyroidism is around 32% in vitiligo patients. Autoimmune thyroid disease is present in around 34% of vitiligo patients. Here we present a case of a 40-year-old male with a history of vitiligo who came with reports of whole body examinations along with history of facial puffiness, bilateral lower limb swelling, generalized body weakness, weight gain, and was diagnosed as hypothyroidism after doing thyroid function tests. The patient was started on Tab thyroxine which was gradually tapered. The patient was symptomatically better after the treatment. Conclusion based on the study is vitiligo patients should be screened for thyroid disease for early detection and earlier management of complications